2020
DOI: 10.1007/s00330-020-06860-3
|View full text |Cite
|
Sign up to set email alerts
|

CT features of novel coronavirus pneumonia (COVID-19) in children

Abstract: A serious epidemic of COVID-19 broke out in Wuhan, Hubei Province, China, and spread to other Chinese cities and several countries now. As the majority of patients infected with COVID-19 had chest CT abnormality, chest CT has become an important tool for early diagnosis of COVID-19 and monitoring disease progression. There is growing evidence that children are also susceptible to COVID-19 and have atypical presentations compared with adults. This review is mainly about the differences in clinical symptom spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
3
11

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(145 citation statements)
references
References 42 publications
8
118
3
11
Order By: Relevance
“…57 Normal findings on chest CT were observed in pediatric patients with mild COVID-19 illness; however, few of them had disease progression on CT scan showing more localized GGO extent, lower GGO attenuation, and relatively rare interlobular septal thickening. 5 Feng et al reported smaller nodular GGO in COVID-19 pediatric patients. However, other features such as interlobular septa thickening, consolidation, GGO with consolidation have also been observed.…”
Section: Imaging Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…57 Normal findings on chest CT were observed in pediatric patients with mild COVID-19 illness; however, few of them had disease progression on CT scan showing more localized GGO extent, lower GGO attenuation, and relatively rare interlobular septal thickening. 5 Feng et al reported smaller nodular GGO in COVID-19 pediatric patients. However, other features such as interlobular septa thickening, consolidation, GGO with consolidation have also been observed.…”
Section: Imaging Findingsmentioning
confidence: 98%
“…Low risk consists of people in endemic areas outside the source of epidemic. 5 COVID-19 clinical manifestations in children may be less severe compared with adults. This may be related to both host factors and exposure.…”
Section: Introductionmentioning
confidence: 99%
“…成人のCOVID–19確定患者について,初診時のPCR検査とCT検査による感度はそれぞれ84.6%,97.2%であったとの報告がある 。CT検査所見では肺野背側および末梢側に出現するground–glass opacification(GGO)とよばれる間質陰影が特徴といわれるが , ,さらに小児の特徴的所見として,肺葉をまたがず,より限局した範囲に淡い陰影として出現するGGO や,haloを伴う浸潤影 が報告されている。15歳未満のCOVID–19確定患者15人において,無症状であった8人のうち7人(初診時4人,経過中3人)にGGOを認めたという報告もあり ,小児においてもPCR検査とCT検査を合わせて用いることでより感度の高い診断ができる可能性がある。…”
Section: 小児におけるCovid–19の臨床像unclassified
“…16 Chest CT abnormalities can be found in patients with negative RT-PCR. 26 On the contrary, a variable proportion of symptomatic children with COVID-19 may have a negative chest CT. 20 Besides, in the early studies published in Chinese and assessed in a systematic review by Duan et al, 20 Chinese children with COVID-19 exhibited specific imaging features on chest CT, different from those described in adults. 19,24 The scope of the present systematic review is to analyse the recent studies that appeared in the English literature focusing on the chest CT features at diagnosis in children with RT-PCR-confirmed COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although CT studies on patients with COVID-19 included a variable number of children and adolescents, studies focusing on COVID-19 infection in children are limited and performed in small populations. [19][20][21][22][23][24] In adults with COVID-19, chest CT abnormalities might appear before clinical symptoms, 25 and be disproportionately severe. 16 Chest CT abnormalities can be found in patients with negative RT-PCR.…”
Section: Introductionmentioning
confidence: 99%